2005
DOI: 10.1139/x04-177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire severity on early development of understory vegetation

Abstract: Four boreal mixedwood stands burned by the 1999 Black River wildfire in southeastern Manitoba were sampled to examine the effects of fire severity on early regeneration dynamics of understory vegetation. In each stand, three fire severity classes (scorched, lightly burned, and severely burned) were identified based on the degree of forest floor consumption, and six plots per severity class were randomly selected. Variation in fire severity significantly affected the initial regeneration of the understory plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 30 publications
6
83
2
1
Order By: Relevance
“…Although VHR data have been mainly used for assessing burn severity, there remains a need to explore the interrelationships between remotely-sensed measurements and the physical/ecological processes that the CBI index infers [3]. So far, a limited number of studies have found statistical correlations between fire severity metrics, topography, VHR satellite data, and ecosystem responses [9,28,36,37]. This has generated the need for more studies focused on the understanding of these relationships.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Although VHR data have been mainly used for assessing burn severity, there remains a need to explore the interrelationships between remotely-sensed measurements and the physical/ecological processes that the CBI index infers [3]. So far, a limited number of studies have found statistical correlations between fire severity metrics, topography, VHR satellite data, and ecosystem responses [9,28,36,37]. This has generated the need for more studies focused on the understanding of these relationships.…”
Section: Study Areamentioning
confidence: 99%
“…So far, a limited number of studies have found statistical correlations between fire severity metrics, topography, VHR satellite data, and ecosystem responses [9,28,36,37]. This has generated the need for more studies focused on the understanding of these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Fires are ecologically important disturbances (Bond et al, 2005) and their effects on plant and animal communities as well as soil biogeochemistry have been widely studied (Certini, 2005;Wang and Kemball, 2005;Ferrenberg et al, 2006). Recent work has also shown that fire induces microbial community shifts characterized by an increase in the relative abundance of Firmicutes and/or b-proteobacteria and an increase in the ratio of bacteria to fungi (Yeager et al, 2005;Smith et al, 2008;Waldrop and Harden, 2008;Bárcenas-Moreno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators described post-fire soil conditions simply as burned or unburned [30,31], while others focused on select conditions within the range of post-fire outcomes [32][33][34] (Table 1). The least severely burned categories contained evidence of fire, but with the forest floor intact [35][36][37]. Moderately severe burned categories described a wide range of conditions from some litter present to all surface organic material consumed.…”
Section: Resultsmentioning
confidence: 99%